Peningkatan Kapasitas Kebijakan Dana Desa dalam Mengentaskan Kemiskinan - Titi Darmi; Iqbal Miftakhul Mujtahid (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
Poverty is not a descent or a destiny, poverty is an impact rather than a regional manager not doing what it should. This study aims to analyze the policy of village funds as an effort to step up poverty, focus the study on Sido Luhur village in Seluma District. The research method is qualitative, primary and secondary data source. The research informants are the Village Head, Village Secretary, Village Office (Kadus), members of the Village Consultative Body (BPD) and Community Leaders. The result of the research shows that the policy of village fund has contributed significantly to the progress of Sidohulur village. However, fund policy has not been instrumental in helping to reduce poverty level either in Sido Luhur village or in Seluma Regency by macro.Keywords: Policy, Village Fund, Poverty Alleviation, New Autonomous Region